(untitled) (Research, Society and Development, 2021)
The present work aimed to characterize morphologically fruits and seeds of angico (Anadenanthera colubrina (Vell.) Brenan) and to test different methods for overcoming dormancy in order to improve and standardize seedling emergence. The study was carried out in the Science laboratory of the State University of Piauí. The germination percentage, germination speed index and average germination time were evaluated. The data were subjected to analysis of variance and the comparison between the means was made by the Tukey test at 5% significance. Data analysis was performed using the SISVAR statistical software. First, the biometrics of the fruits and seeds were performed, the treatments used to overcome dormancy were: control (T1), immersion in hot water at a temperature of 100 ° C for 10 minutes (T2), thermal shock (T3), soaking in water for 24 hours (T4), soaking in water for 48 hours (T5), chemical scarification with 98% sulfuric acid for 30 minutes (T6), chemical scarification with sulfonic acid for 30 minutes (T7) and chemical scarification with acid muriatic for 30 minutes (T8). The treatment with sulfuric acid have promoted the highest germination rate with a rate equal to 87, 49%. The germination of Anadenanthera colubrina seeds has a rapid development and is considered epigeal, where germination occurred 3 days after sowing. Sulfuric acid treatment has proved to be effective in promoting the emergence and breaking dormancy of "Angico" seeds. The analysis of morphobiometry found that this study may contribute to the identification and characterization of the studied species.